Persepsi Siswa Teknik Permesinan Mengenai Kesehatan dan Keselamatan Kerja di Workshop Permesinan SMK Dhuafa Padang - Kifli, Rafi Febrianto; Syahri, Budi; Purwantono, Purwantono; Efendi, Fiki (Lembaga Yasin AlSys, 2024)
This research aims to determine the perceptions of mechanical engineering students regarding occupational health and safety in the machinery workshop of SMK Dhuafa Padang. This research method uses this research using quantitative data. Based on this quantitative data, it will be possible to describe the perception of mechanical engineering students regarding occupational health and safety in the Dhuafa Padang Vocational School machining workshop. This research was conducted in January–February 2024 at SMK Dhuafa Padang. The total population is 60 students. The sampling technique used was a total sampling of 60 students. Based on the research results, it can be concluded that students' perceptions regarding occupational health and safety at the Dhuafa Padang Vocational School's Machinery Workshop on student health and safety indicators are 84%, so they are included in the Good category. Students' perceptions regarding occupational health and safety in the Dhuafa Padang Vocational School's Machinery Workshop on work environment health and safety indicators are 80.9%, so they are included in the Good category. Student Perceptions Regarding Occupational Health and Safety in the Machinery Workshop of SMK Dhuafa Padang on the tool health and safety indicators are 78.2%, so it is included in the fair category. Student Perceptions Regarding Occupational Health and Safety in the Machinery Workshop of SMK Dhuafa Padang on Material Health and Safety Indicators are 79.6%, so it is included in the fair category.